Effect of Nozzle Tip’s Variation to The Duration and OXY-LPG Gas Consumptions Using Manual CuttingMethods in Shipyards - Mardhotillah, Zahro Wanda; Kristiyono, Tri Agung; Aditya, Bagus Kusuma (Universitas Jember, 2022)
In maritime industry, especially shipbuilding in Indonesia, various of cutting processes are implemented, which one is Gas Manual Cutting. Generally, gas requirements and duration of plate cutting processes are calculated based on previous work experience. The use of different nozzle tips by the operator will affect to gas consumption and cutting duration in each process. The purpose of this study was to determine the effect of variations in the tip-nozzle size on the duration and OXY-LPG gas requirements in manual plate cutting. The research was conducted using an experimental-based research with linear regression analysis using the ANOVA method. Based on the results of data analysis, it can be known that the larger the diameter of the nozzle tip, the requirements for OXY-LPG gas will increase by following the equation ????=0,1117????+0,3533 for Oxygen and ????=0,025????+0,0489 for LPG. Meanwhile, the larger of nozzle tip diameter can cause a decrease in the cutting duration required by following the regression equation ????=−28,603????+293,01.